Pengembangan Modul Pembelajaran Fisika Berbasis Kearifan Lokal Pada Alat Musik Tradisional Untuk Meningkatan Pemahaman Konsep - Panis, Isabel Coryunitha; Mukin, Maria Ursula Jawa; Uran, Yosefa Lama (Universitas Negeri Malang, 2023)
The purpose of the development research that has been carried out is to obtain learning modules that are used in Physics learning in class XI IPA, especially in Sound material using traditional musical instruments. The results of this development product are printed teaching materials that are suitable for use by high school students. Some of the development steps that have been carried out include: preparation of development plans and validity tests by experts. Media and material validity tests have been carried out by fulfilling the appropriate criteria so that they can be applied as one of the learning media used in class to increase student understanding. Conclusions based on research results are learning media based on local wisdom, especially from traditional musical instruments developed in the form of printed modules, which are still suitable for use in classroom learning, especially in an effort to increase students' understanding of the material. The advice given by further research is to be able to develop advanced learning media based on local wisdom but based on traditional games in the community.AbstrakTujuan pengembang ini adalah untuk dapat menghasilkan modul pembelajaran Fisika berbasis kearifan lokal pada alat music tradisional yang layak digunakan oleh siswa SMA Kelas X. Produk modul pembelajaran yang dihasilkan berupa modul cetak pada mata pelajaran Fisika, materi Bunyi. Prosedur pengembangan modul pembelajaran Fisika berbasis kearifan lokal pada alat music tradisional yang dapat meningkatkan pemahaman konsep siswa SMA kelas X ini mengunakan model Borg and Gall. Tanggapan ahli media dan ahli materi terhadap modul pembelajaran mendapatkan respon positif dengan prosentase kelayakan sebesar 90,37 % untuk media, dan sebesar 85,99 % untuk materi yang disajikan. Secara umum produk modul pembelajaran Fisika berbasis kearifan lokal pada alat music tradisional untuk dapat meningkatkan pemahaman konsep siswa SMA kelas X layak digunakan dalam pembelajaran.